Analisis Pengembangan Smart City Di Kota Tanjungpinang - Putri Aisya Damayanti; Ramadhani Setiawan; Firman Firman (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
This research discusses the readiness of Tanjungpinang city in developing a smart city. The objective is to understand and describe the preparations made by Tanjungpinang city in developing a smart city and to identify inhibiting factors influencing the implementation of a smart city in Tanjungpinang. A qualitative descriptive methodology was employed, utilizing data collection techniques such as interviews with the City Planning and Development Agency (BAPELITBANG) of Tanjungpinang, observations, and secondary document analysis to reinforce research data. Data analysis was conducted using descriptive and thematic analysis techniques. The research used 10 criteria for the readiness of developing countries in implementing a smart city to measure the obstacles faced by Tanjungpinang in becoming a smart city. The results indicate that Tanjungpinang has prepared itself to become a Smart City through various efforts but still faces significant obstacles. Critical obstacles include technological illiteracy, a lack of skilled human resources in IT, suboptimal technological infrastructure, insufficient basic infrastructure, and adequate financial support. Solutions require strategic steps, close collaboration, and a holistic approach. Education and training are necessary to address technological illiteracy, investments in IT human resources, optimization of technological infrastructure, improvement of basic infrastructure, and the search for sustainable financing models. By overcoming these obstacles, Tanjungpinang can realize effective smart city solutions, improve the quality of life for its citizens, and achieve sustainable development goals.